Alopecia areata in patients with systemic lupus erythematosus treated with belimumab: a plausible association. (April 2020) - Shamriz, O; Yahia, S H; Ramot, Y; Agmon-Levin, N; Tal, Y
Belimumab, an anti-B-lymphocyte stimulator monoclonal antibody, was recently approved for the treatment of systemic lupus erythematosus. Alopecia areata is characterized by an acute immune-mediated hair loss. Herein, we report on three adult systemic lupus erythematosus patients who developed alopecia areata in association with belimumab treatment. Alopecia areata was resolved in all three patients and belimumab was discontinued in two of them. Thus, in the current report, we explore the plausible link between alopecia areata and belimumab.